Evaluation Of The Use Of Mdi And Dpi Inhaler Preparations In Chronic Obstructive Pulmonary Disease (Copd) Patients At Uns Hospital - Reihan Rendika; Hidayah Apriliawan; Aprilia Puteri Santika (International Journal of Health Engineering and Technology, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic lung disease characterized by progressive and not fully reversible airflow limitation. One of the main therapies for COPD is inhaled medication delivered through Metered Dose Inhalers (MDI) and Dry Powder Inhalers (DPI). The success of therapy is strongly influenced by the correctness of inhaler technique, as improper use can reduce drug deposition in the airways and affect clinical outcomes. This study aimed to evaluate the accuracy of MDI and DPI inhaler use and its relationship with the FEV₁/FVC ratio in COPD patients at RS UNS. This study employed a non-experimental design with a cross-sectional approach. A total of 100 COPD patients who met the inclusion criteria were selected using purposive sampling. Sociodemographic data and inhaler-use accuracy were obtained through direct interviews, while FEV₁/FVC values ​​were collected from medical records. The data were analyzed using the Chi-Square test with a significance level of α = 0.05. The results showed that most respondents were over 45 years old (80%) and female (56%). The level of correct inhaler use was low in both MDI users (22.2% correct) and DPI users (13.2% correct). There was no significant relationship between sociodemographic factors and inhaler-use accuracy (p > 0.05). However, a highly significant relationship was found between inhaler-use accuracy and achievement of the FEV₁/FVC ratio (p < 0.001), in which all patients with correct inhaler technique achieved the target FEV₁/FVC. In conclusion, appropriate inhaler technique plays a crucial role in achieving optimal pulmonary function outcomes in COPD patients. Therefore, continuous education and regular evaluation of inhaler technique are essential to support the success of COPD therapy.